2020
DOI: 10.1088/1755-1315/456/1/012053
|View full text |Cite
|
Sign up to set email alerts
|

Response of groundnut promising lines to various environments

Abstract: The aims of this study was to evaluate the response of groundnut promising lines grown in various environments. A number of 18 groundnut lines and 2 checked cultivars were grown in 3 different environments i.e. lowlands with heavy and loamy soil texture at Ngawi and Banyuwangi Districts, and dry alkaline soils at Tuban District. A randomized block design with three replicates was applied in each site. Each genotype was planted in a 2 m x 5 m plot size with plant spacing of 40 cm interrows x 10 cm intrarow, 1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Uge et al [13] tested several peanut genotypes and found similar results. Different results were shown by Purnomo and Rahmiana [6] , who reported that there were genotypes that had resistance to leaf rust. It was further reported that these genotypes have high yield potential similar to that of the comparison varieties Hypoma 1 and Katana 1.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Uge et al [13] tested several peanut genotypes and found similar results. Different results were shown by Purnomo and Rahmiana [6] , who reported that there were genotypes that had resistance to leaf rust. It was further reported that these genotypes have high yield potential similar to that of the comparison varieties Hypoma 1 and Katana 1.…”
Section: Introductionmentioning
confidence: 67%
“…P. arachidis infection causes a decrease in seed yield and oil quality. Early infection with P. arachidis during the growth period causes economic losses of up to 57% [5] , whereas mixed infections with other foliar disease pathogens can result in yield losses of up to 60% [6] . Several techniques for controlling leaf rust pathogens have been used, including integrated control, intercropping, botanical and synthetic pesticides [7] , induction of biotic resistance [8] , and application of NPK fertilizer [9] .…”
Section: Introductionmentioning
confidence: 99%